Pengaruh Luas Permukaan Dializer Terhadap Capaian Adekuasi Dialisis pada Penderita Haemodialisis di Rumah Sakit PKU Muhammadiyah Yogyakarta - Chayati, Nur (IJNP (Indonesian Journal of Nursing Practices), 2014)
General appearance of weakness, skinny, high blood pressure, anemia, itches, darkness skin color and nausea showing inadequate hemodialysis clinically. Based on literature review there are some factors directly infl uencing on adequate hemodialysis, one of them is dialyzer surface area. The research aimed to study the effect of dialyzer surface area on dialysis adequacy on hemodialysis patient in PKU Muhammadiyah Hospital Yogyakarta from May until June 2013. Cross sectional study was done involving 90 respondents through purposive sampling method. The hemodialysis adequacy counted by Kt/V formula. Data was taken during the second session of hemodialysis. The data were examined with Kruskal Wallis. Mean dialysis adequacy was 1,36Â±0,377. The statistic test result revealed no signifi cant correlation on dialyzer surface area with dialysis adequacy (p=0.880).Key words: adequacy, dialyzer, hemodialysis